ON SOME ASPECTS OF BIOLOGY OF PRIACANTHUS MACRACANTHUS (CUVIER) - Rao, T Appa (Indian Journal of Fisheries, 2011)
Analysis of stomach contents of Priacanthus macracanthus revealed that crustaceans and toleosts are the chief constiuents of food; Penaeus sp, Metapenaeus sp and Solenocera sp being the most important items. From frequency distributions of intraovarian eggs, spawning period seems to be from November to January. The ratio between males and females is not constant. Size frequency distribution showed that the species grows at the rate of 10 mm per month.